Lack of association between the TMPRSS6 gene polymorphism (rs855791) and anemia: a comprehensive meta-analysis - Jethendra Kumar Muruganantham; Ramakrishnan Veerabathiran (Hematology, Transfusion and Cell Therapy)
Background: Anemia affects around 1.6 billion people worldwide and presents a significant challenge for healthcare providers. Despite the hemoglobin concentration being commonly used for diagnosis, identifying underlying causes remains challenging, particularly in vulnerable groups like children under five and pregnant women. Genetic factors, notably variations in the TMPRSS6 gene, are implicated in iron deficiency anemia, yet the precise relationship with anemia remains unclear. Methods: A thorough literature search was conducted across databases, including Embase, Google Scholar, and PubMed, focusing on studies investigating TMPRSS6 gene polymorphisms and anemia. Thirteen eligible studies, comprising 2082 cases and 2684 controls, underwent meta-analysis using Review Manager 5.4 software. Various genetic models were assessed, including allelic, homozygous, heterozygous, dominant, and recessive, with no significant relationship found between the TMPRSS6 rs855791 polymorphism and anemia. Conclusion: This meta-analysis provides robust evidence suggesting no significant association between the TMPRSS6 rs855791gene polymorphism and anemia. These findings underscore the complexity of genetic factors contributing to anemia and emphasize the importance of the further investigation to unravel the mechanisms underlying this relationship for improved diagnostic and therapeutic approaches.